Sectoral Performance of ESG Enabled Stocks during COVID-19 Pandemic in the Indian Stock Market - Sharma, Prashant; Arora, Geetika; Kalyani, Sushil; Olasiuk, Hanna; Jindal, Padmini (International Journal of Economics and Financial Issues, 2024)
Over past one decade, there is significant rise in Environment, Social and Governance (ESG) enabled investment practices across the globe and Indian economy is no exception to that. The ESG-enabled investment options provide better investment avenues for investment for retail and institutional investors by ensuring the long-term sustainability of the business. The present study tries to assess whether there is any impact of ESG scores on performance of stocks at the time of COVID-19 pandemic period. The study compares the performance of stocks with high ESG score vis-à-vis stocks with low ESG scores during COVID-19 period for different sectors of Indian stock market. The study considers the data of 312 sample firms listed on BSE 500 index. The event study methodology is used to assess the impact of COVID-19 on Indian stocks. The stocks were further divided into three categories high score (top 30% of firms), medium (middle 40% of firms) and low (bottom 30% of the firms). The results of the study suggest that the investors were more confident about the performance and revival of firms that carry high ESG scores than firms with low ESG scores. The investors are confident about the long-term prospects and sustainability of the firms, and they tend to hold their investment in the firms with high ESG scores.